Avaliação de custo efetividade entre imunossupressores utilizados no transplante renal: um estudo farmacoepidemiológico e farmacoeconômico sobre o programa nacional de medicamentos excepcionais no SUS de 2000 a 2004 - Augusto Afonso Guerra Junior (2010)
Background: In Brazil, the National Health System (SUS) is responsible for almost all renal transplants. SUS protocols recommend using cyclosporine, in association with azathioprine and corticosteroids, to maintain the immunosuppression essential for successful renaltransplant (RT). Alternatively, cyclosporine (CsA) can be replaced by tacrolimus (Tac). Objective: The aim of this thesis study was to evaluate the cost-effectiveness of therapeutic schema involving cyclosporine or tacrolimus after renal transplant during a 60 month followup period.Methods: This study consisted of an historical cohort study, from 2000 to 2004, of 5686 patients who underwent renal transplant and made use cyclosporine or tacrolimus, identified by probabilistic record linkage in databases of the Brazilian National Health System (SUS). Article-1 used the SUS perspective to make an economic analysis about ambulatory, hospital and medications resources used per patient and therapeutic groups of CsA. or Tac. Article-2 shows univariate and multivariate analysis using Cox model examining factors associated with progression to treatment failure. The effectiveness was established by the survival ofpatients evaluated by the Kaplan-Meier method. Article-3 has performed a cost-effectiveness evaluation in SUS perspective, carried out from the historical cohort from 2000 to 2004, with 2022 patients undergoing kidney transplantation paired in 1:1 with cyclosporine or tacrolimus. Results: After 60 months follow-up a superior expenditure has been observed among patients of northeast region hospitals cadaveric donor, in dialyses for >24 months before RT and to the group of Tac. A higher expenditures with hospital, ambulatory and medicines resources were observed among patients in therapeutic schemes with Tac when compared to whose with CsA for RT maintenance. Most of the patients were male, aged = 38 years, for whom the most frequent primary diagnosis of chronic renal failure (CRF) were glomerulonephritis/nephritis. Higher risk of treatment failure was associated with: therapeutic regimen (tacrolimus, HR = 1.38, 95%CI = 1.14 to 1.67), patient age at transplantation (additional year, HR = 1.01, 95%CI = 1.00 to 1.02), donor type (deceased, HR = 1.60, 95%CI = 1.35 to 1.89), median time of dialysis prior transplantation (>24 months, HR 1.57,95%CI = 1.34 to 1.83) and primary CRF diagnosis (diabetes, HR = 1.54, 95%CI = 1.09 to 2.17). Cost-effectiveness points to the dominance of cyclosporine-based regimens compared to tacrolimus, since the total costs per patients with CsA for 1st year and for the 5 years followed are smaller, with a higher number of life years gained to this group. Conclusions: There was a higher total expenditure on hospital resources, medical services and medicines for the RT in patients with regimens with Tac when compared with the CsA group. There was also a 1.38 times higher risk of treatment failure among users of tacrolimus compared to cyclosporine. After matching patients of CsA and Tac in 1:1 there was no evidence for improved survival of patients on Tac. The economic evaluation showed that CsA-based regimens were more cost-effective (dominant) than with Tac. The results presented shows the importance of the use of clinical protocols and therapeutic guidelines drugs used in renal transplantation. Despite limitations, the historical cohort proved useful for studying the effects of exposure and the costs financed by the SUS.